2016
DOI: 10.1111/cdev.12545
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Transmission of Educational Attitudes in Chinese American Families: Interplay of Socioeconomic Status and Acculturation

Abstract: This longitudinal study examined the influence of parents’ educational attitudes on adolescents’ educational attitudes and identified antecedents (i.e., parent education, family income, and parent acculturation), consequences (i.e., academic achievement and engagement), and a potential moderator (i.e., adolescent acculturation) of the transmission process. The sample was 444 Chinese American mothers, fathers, and adolescents (12–15 at W1). Using path analysis, this study found significant two-way interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 64 publications
4
6
0
Order By: Relevance
“…In line with previous research, we hypothesized that there will be varying levels of acculturation among the families (Oades-Sese and Li, 2011;Shen et al, 2016). Additionally, we hypothesize that on average DLL children will have low oral language abilities in both English and HL, similar to past studies (Hammer et al, 2014).…”
Section: What Are the Levels Of Acculturation For First-generationsupporting
confidence: 72%
See 1 more Smart Citation
“…In line with previous research, we hypothesized that there will be varying levels of acculturation among the families (Oades-Sese and Li, 2011;Shen et al, 2016). Additionally, we hypothesize that on average DLL children will have low oral language abilities in both English and HL, similar to past studies (Hammer et al, 2014).…”
Section: What Are the Levels Of Acculturation For First-generationsupporting
confidence: 72%
“…Cultural orientation may differ depending on a variety of factors including social class, reasons for immigration, how long the parent has been in the host country, how much support there is in the neighborhood and surrounding communities, and access to resources (Zhang, 2010). Past research has shown a wide range of acculturation levels for immigrant families (e.g., Oades-Sese and Li, 2011;Shen et al, 2016). Although there is variation in acculturation levels, studies with Chinese immigrant families in the United States have found that the majority of parents held on to their HL and culture because HL was the only communication tool for parents who had limited English proficiency (Zhang, 2010).…”
Section: Parental Acculturationmentioning
confidence: 99%
“…The average of the father's and mother's highest education level was taken to indicate parental education level. Parental educational level was included as a covariate given its relation to adolescent depressive symptoms (Costello, Swendsen, Rose, & Dierker, 2008) and academic performance (Shen, Kim, & Wang, 2016). Adolescent gender and nativity were also included as covariates.…”
Section: Methodsmentioning
confidence: 99%
“…Reciprocally, more acculturated parents are likely more accustomed to the mainstream educational system, which may benefit their children; separate from paternal education and family income, more acculturated Chinese American fathers have adolescents who get better grades (Kim, Wang, Chen, Shen, & Hou, 2015). Educational attitudes are more closely tied to educational achievement among more acculturated Asian American mothers (Shen, Kim, & Wang, 2016). More acculturated Latina American mothers read more (Raikes et al, 2006), provide a more cognitively stimulating home environment (M.…”
Section: Specificity Principle: Setting Conditionmentioning
confidence: 99%